The new Oxford picture dictionary - Parnwell, E. C.; Parnwell, E. C.; Burns, Raymond, 1924- (New York, NY : Oxford University Press, 1989)
Teaches English as a second language to Spanish speakers through the use of pictures dealing with everyday topics such as the body, post office, law, travel, and family.
Rev. ed. of: Oxford picture dictionary of American English. English/Spanish ed. 1978.
Includes index.
Keywords: Picture dictionaries, English; English language -- United States -- Dictionaries; Americanisms -- Dictionaries; English language -- Spanish. -- Spanish; English language -- Spanish. -- Spanish